2017
DOI: 10.1016/j.virol.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro exposure system for study of aerosolized influenza virus

Abstract: Infection of adherent cell monolayers using a liquid inoculum represents an established method to reliably and quantitatively study virus infection, but poorly recapitulates the exposure and infection of cells in the respiratory tract that occurs during infection with aerosolized pathogens. To better simulate natural infection in vitro, we adapted a system that generates viral aerosols similar to those exhaled by infected humans to the inoculation of epithelial cell monolayers. Procedures for cellular infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…At 33°C, ID 50 s were similar, except in the case of the NL/230 virus, which had an ID 50 of 83 PFU at 33°C, compared to 10 PFU at 37°C. Consistent with data for respiratory cells (18), temperature had little effect on the growth of the seasonal virus Pan/99, whereas the growth of the avian viruses was attenuated at the lower temperature. The effects of temperature on the curve shape were similar across inoculation doses, but differences in peak titers were greater at lower exposure doses, possibly because the low dosage delayed replication at both temperatures such that titers had not plateaued by 96 h postinfection.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…At 33°C, ID 50 s were similar, except in the case of the NL/230 virus, which had an ID 50 of 83 PFU at 33°C, compared to 10 PFU at 37°C. Consistent with data for respiratory cells (18), temperature had little effect on the growth of the seasonal virus Pan/99, whereas the growth of the avian viruses was attenuated at the lower temperature. The effects of temperature on the curve shape were similar across inoculation doses, but differences in peak titers were greater at lower exposure doses, possibly because the low dosage delayed replication at both temperatures such that titers had not plateaued by 96 h postinfection.…”
Section: Resultssupporting
confidence: 84%
“…Although ocular aerosol challenge has been used in animals, to our knowledge, this inoculation method has not been used with human ocular cells or tissues. We previously found that primary human alveolar epithelial cells were less susceptible to infection with certain viruses when inoculated via aerosol than when inoculated by more traditional methods (18). To determine whether a similar phenomenon might explain why both seasonal and avian respiratory viruses, previously shown to productively infect multiple ocular cell types (8,9,11,12,23), rarely establish ocular infection in humans, we inoculated corneal epithelial cells by the aerosol route.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferrets have represented a critical in vivo model for these activities, and it is likely that the role this species plays in our understanding of influenza virus pathogenicity, transmissibility, and tropism will only increase in the coming years. Advances in cell culture models have sought to more closely emulate the complexity of in vivo models; examples include the development of physiologically relevant inoculation routes and the generation of organoid tissues that are representative of the human respiratory tract (Creager et al 2017;Hui et al 2018). Similarly, ex vivo primary differentiated cultures of ferret tissue-specific cells provide an additional link between in vivo and in vitro experimentation, supporting and enhancing studies investigating viral pathogenicity and tropism (Zeng et al 2013(Zeng et al , 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Here, H1N1‐containing aerosols with a mass median aerodynamic diameter of 1.27 ± 0.61 μm were generated by an animal nose‐only aerosol exposure device. In addition, some comparative studies have demonstrated that compared with droplet instillation, inhalation of H5N1‐ and H7N9‐containing aerosols represent a more natural route of human exposure . Therefore, the aerosol inhalation method, which directly delivers H1N1‐containing aerosols to the noses of exposed BALB/C mice via a nose‐only aerosol exposure device, was selected to mimic the natural route of human infection with influenza A(H1N1).…”
Section: Introductionmentioning
confidence: 99%